2014
DOI: 10.1111/tri.12443
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bright light therapy on sleep and circadian rhythms in renal transplant recipients: a pilot randomized, multicentre wait-list controlled trial

Abstract: SummaryThis study assessed the effect and feasibility of morning bright light therapy (BLT) on sleep, circadian rhythms, subjective feelings, depressive symptomatology and cognition in renal transplant recipients (RTx) diagnosed with sleep-wake disturbances (SWD). This pilot randomized multicentre wait-list controlled trial included 30 home-dwelling RTx randomly assigned 1:1 to either 3 weeks of BLT or a wait-list control group. Morning BLT (10 000 lux) was individually scheduled for 30 min daily for 3 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…This descriptive analysis was based on the baseline data of a multicentre randomised wait-list controlled design study (Burkhalter et al, 2015). The intervention group completed 3 weeks of baseline measurement, followed by 3 weeks of morning bright light therapy, then a 3-week post-treatment assessment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This descriptive analysis was based on the baseline data of a multicentre randomised wait-list controlled design study (Burkhalter et al, 2015). The intervention group completed 3 weeks of baseline measurement, followed by 3 weeks of morning bright light therapy, then a 3-week post-treatment assessment.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the overview of possible mechanisms of desynchronisation of sleep-wake rhythms, leading to sleep disturbances in dialysis patients (Parker, 2003) and in patients with chronic kidney disease (Russcher et al, 2012), we assume similar mechanisms for RTx recipients. The only significant finding in the intervention group after bright light therapy, applied each morning to regularise nocturnal sleep, was a phase advance in both get-up time and bedtime in the actimetry data (Burkhalter et al, 2015). However, only very few participants had a measureable DLMO, which precluded documenting any parallel advance in DLMO after morning light therapy.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…These patients experience insomnia, restless legs syndrome (a neurological disorder), and obstructive sleep apnea (Burkhalter et al 2015). It is suggested to be a result of an innate immune response (Kapsimalis et al 2008, Besedovsky et al 2012 or due to the inflammatory effects generated after transplantation (Castanon-Cervantes et al 2010).…”
Section: Kidney Transplantationmentioning
confidence: 99%
“…It is suggested to be a result of an innate immune response (Kapsimalis et al 2008, Besedovsky et al 2012 or due to the inflammatory effects generated after transplantation (Castanon-Cervantes et al 2010). A human multicenter study (Burkhalter et al 2015) observed that the daytime bright light therapy improved sleep quality and the disorders derived from it. Decreased levels of melatonin were also observed in all patients, and the authors suggested that the intake of β-blockers and acetylsalicylic acid likely interfered with melatonin secretion, as shown in previous studies (Brismar et al 1988).…”
Section: Kidney Transplantationmentioning
confidence: 99%